Analisis Kadar Protein dengan Metode Lowry pada Berbagai Jenis Produk Susu yang Beredar di Lingkungan Universitas Muhammadiyah Surakarta - Sudrajah Warajati Kisnawaty; Sudana Fatahillah Pasaribu; Titik Dwi Noviati; Muhammad Masykuri Abdillah (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
The milk contains bioactive compounds that are beneficial for health. One of bioactive compounds contained in the milk is protein nutrient. Examination of protein levels in foodstuffs can be tested using the Lowry method that considered more sensitive. The purpose of this study was to analyzed the protein levels of various types of dairy products. This research included laboratory research with samples of 5 types of dairy products were sweetened condensed milk with vanilla flavor, fresh cow's milk, vanilla flavored skim milk flour, vanilla flavored full cream milk flour, and plain goat's milk flour. Protein content of samples were tested using the Lowry method with 3 repetitions each. The collected data were tested using One way Anova and Tukey HSD. The results of the examination of protein levels in the sample showed that the highest protein content was vanilla flavored full cream milk flour (8.43%). Meanwhile, the lowest protein content were fresh cow's milk and vanilla flavored sweetened condensed milk, which were 2.86 and 2.87%, respectively. The average protein content in dairy products in the Universitas Muhammadiyah Surakarta was 5.39%. There are significant differences between various types of dairy products on protein content.